2017
DOI: 10.3389/fnmol.2017.00062
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 Protects Dopaminergic Neurons In vitro but Is Dispensable for MPTP-Induced Neurodegeneration In vivo

Abstract: Microglia are involved in physiological as well as neuropathological processes in the central nervous system (CNS). Their functional states are often referred to as M1-like and M2-like activation, and are believed to contribute to neuroinflammation-mediated neurodegeneration or neuroprotection, respectively. Parkinson’s disease (PD) is one the most common neurodegenerative disease and is characterized by the progressive loss of midbrain dopaminergic (mDA) neurons in the substantia nigra resulting in bradykines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Our results revealed controversial findings for the anti-inflammatory marker IL-4 in peripheral blood and CSF, possibly suggesting dual functions in the CNS. IL-4 shapes microglial functions to promotes the survival of dopaminergic neurons in animal models 32 , which underlines the therapeutic potential of IL-4 administration in PD. In addition, IL-4 promotes neurodegeneration in proinflammatory rat models by contributing to microglial activation, IL-1β production, and BBB disruption 33 .…”
Section: Discussionmentioning
confidence: 88%
“…Our results revealed controversial findings for the anti-inflammatory marker IL-4 in peripheral blood and CSF, possibly suggesting dual functions in the CNS. IL-4 shapes microglial functions to promotes the survival of dopaminergic neurons in animal models 32 , which underlines the therapeutic potential of IL-4 administration in PD. In addition, IL-4 promotes neurodegeneration in proinflammatory rat models by contributing to microglial activation, IL-1β production, and BBB disruption 33 .…”
Section: Discussionmentioning
confidence: 88%
“…The current results are incompatible to our previous report that IL-4 enhances neuronal survival after traumatic spinal cord injury and in LPS-treated cortex in vivo by regulating neuroinflammation [ 12 47 ]. Hühner and colleagues have recently reported that exogenous IL-4 protects MPP + -induced degeneration of midbrain DA neurons in vitro , but endogenous IL-4 has no effect on MPTP-induced degeneration of nigrostriatal dopamine neurons in IL-4 knock-out mice in vivo [ 48 ]. On the other hand in the present study, IL-4 contributes to microglial activation, production of IL-1β, and disruption of BBB and astrocytes which subsequently led to the degeneration of DA neurons in the LPS-treated SN in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory cytokine IL-4 is also involved in PD pathology. In mixed neuron-glia culture, inhibition of endogenous microglia-derived IL-4 enhanced MPTPinduced neurotoxicity, and exogenous administration of IL-4 in the mouse MPTP model protects against neurotoxicity, indicating a potential protective role of IL-4 in PD [348]. In addition to IL-4 and IL-10, the pleiotropic M2 cytokine TGF-β mediates neuroprotective functions in inflammation and neurotoxin PD models; it limits M1 microglial activation and dopaminergic neurodegeneration [349,350].…”
Section: Microglia Phenotypes In Pd M1 and M2 Microglia In Pdmentioning
confidence: 99%